2022
DOI: 10.3390/ijms23116252
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Antagonizes Cadmium-Induced Inflammation and Oxidative Stress via Suppressing the Interplay between NLRP3 Inflammasome and HMGB1/NF-κB Pathway in Duck Hepatocytes

Abstract: Cadmium (Cd) is a toxic heavy metal that can accumulate in the liver of animals, damaging liver function. Inflammation and oxidative stress are considered primary causes of Cd-induced liver damage. Selenium (Se) is an antioxidant and can resist the detrimental impacts of Cd on the liver. To elucidate the antagonism of Se on Cd against hepatocyte injury and its mechanism, duck embryo hepatocytes were treated with Cd (4 μM) and/or Se (0.4 μM) for 24 h. Then, the hepatocyte viability, oxidative stress and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…In the present study, our molecular and immunohistochemical findings revealed that the Cd-intoxicated group markedly upregulates the expression level of HSP70, TLR4, and NF-κB. These findings come in agreement with [123] who reported that Cd significantly promoted the expression level of the TLR4/NF-κB pathway in duck embryo hepatocytes, and also [124], exhibited that Cd enhanced the expression of HMGB1 downstream mediators, including TLR-4 and NF-κB which exacerbated the damaging effects of Cd in exposed tissues via stimulating the release of several inflammatory cytokines. Interestingly [125], revealed that Cd could induce adrenal damage through activation of TLR4/ NF-κB-mediated inflammatory responses which play an essential role in Cd-induced toxic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, our molecular and immunohistochemical findings revealed that the Cd-intoxicated group markedly upregulates the expression level of HSP70, TLR4, and NF-κB. These findings come in agreement with [123] who reported that Cd significantly promoted the expression level of the TLR4/NF-κB pathway in duck embryo hepatocytes, and also [124], exhibited that Cd enhanced the expression of HMGB1 downstream mediators, including TLR-4 and NF-κB which exacerbated the damaging effects of Cd in exposed tissues via stimulating the release of several inflammatory cytokines. Interestingly [125], revealed that Cd could induce adrenal damage through activation of TLR4/ NF-κB-mediated inflammatory responses which play an essential role in Cd-induced toxic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress, inflammatory process, apoptosis and antioxidation system could interact (Table 4). ROS leads to oxidative stress which could activate the inflammatory pathways, and in turn will positively lead to further generation of ROS 67 . Studies have shown that HM's like Pb, Cd, or As could generate ROS, lead to oxidative stress and subsequent activation of the inflammatory and apoptotic processes 1,3,5,51 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS leads to oxidative stress which could activate the inflammatory pathways, and in turn will positively lead to further generation of ROS. 67 Studies have shown that HM's like Pb, Cd, or As could generate ROS, lead to oxidative stress and subsequent activation of the inflammatory and apoptotic processes. 1,3,5,51 These interactive effects manifested in our correlation studies.…”
Section: Histopathological Studies Of the Livermentioning
confidence: 99%